Il caso “L’Iguana”: scelte editoriali, scarti, misteri e soluzioni da un testo di Anna Maria Ortese - Marco Ceravolo (Altre Modernità, 2020)
Anna Maria Ortese’s L’Iguana is one of the most enigmatic pieces of her entire work. At the National Archive of Naples, where all Ortese’s unpublished works are kept, one may find a large collection of papers on L’iguana: scraps, notes and several discarded finals. Initially, in 1963, eight chapters of the book were published by the magazine “Mondo”. L’Iguana went through a difficult destiny: three different publishing houses contended over its publication, and finally the novel was published by Vallecchi Editions in 1965. Later on, in 1980, Ortese wrote to Natalia Ginzburg, mentioning a “new version of Iguana, entitled Miseria e solitudine di una Iguana” (Spadaccini, Archivio di Stato di Napoli, 2006, doc. 54). The present study starts from the editorial case of the novel, passing through the investigation of the original papers from Fondo Ortese: our attempt is to examine Anna Maria Ortese’s modus operandi, taking in consideration the different editions, revisions and the discarded finals. In order to get a better understanding of this mysterious and grotesque novel, we will follow the notes written by the author, marking the history of the author’s scraps, the reasons which led Ortese to the different ending.